Color-changing smart fibrous materials for naked eye real-time monitoring of wound pH. Issue 16 (20th March 2019) - Pan, Nan; Qin, Juanrong; Feng, Pingping; Li, Zeke; Song, Botao
Abstract : A biocompatible fibrous sensor material with pH-responsive color changing property was designed for real-time monitoring of wound pH. Abstract : Real-time monitoring of wound pH may provide information about the wound healing status and potential bacterial infection. Herein, we integrated the biocompatible color changing substance curcumin into a fibrous material, capable of in situ real-time visually monitoring the wound pH. The results indicate that the curcumin-loaded fibrous mat exhibits an obvious pH-dependent color change from yellow to red brown with a change in pH from 6.0 to 9.0, which can be easily detected by the human naked eye. Moreover, the wound pH conditions can be determined with the aid of a smart phone App after image analysis. Due to their flexibility, the fibrous materials have been further processed into various shapes from 1D to 3D for fitting the irregular wounds. It is believed that smart fibrous materials that can simultaneously real-time monitor the wound pH and repair the wound may change wound management to a convenient and comfortable way.